2013
DOI: 10.1002/anie.201208185
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Activation of 2‐Alkanones through Photo‐Induced α‐Hydrogen Abstraction Mediated by a Dinuclear Ruthenium Tetrahydride Complex

Abstract: The photochemical behavior of transition-metal complexes has long been a fascinating subject that is related to electron transfer processes, specific organotransformations, photosynthesis, and electrochemical conversion of solar energy. Although there are a vast number of studies on the photochemistry of mononuclear complexes, multimetallic systems remain unexplored. [1] In general, in cluster complexes with metal-metal bonds, the lowest unoccupied orbital is an antibonding orbital that is delocalized over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Much more recently, the photochemistry of (Cp*Ru) 2 (μ-H) 4 has been examined. This complex absorbs at 371 nm (ε = 2200 dm 3 mol –1 cm –1 ) and was photochemically inert in THF, but reacted on irradiation at 365 nm with methyl ketones to form (Cp*Ru) 2 (μ-H) 2 (μ–η 4 -CH 2 C­(O)­CHR) + 2H 2 where the bridging ligand is described as oxatrimethylenemethane . The authors propose that the reaction proceeds via an exciplex, although no further evidence is provided.…”
Section: Photochemical Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Much more recently, the photochemistry of (Cp*Ru) 2 (μ-H) 4 has been examined. This complex absorbs at 371 nm (ε = 2200 dm 3 mol –1 cm –1 ) and was photochemically inert in THF, but reacted on irradiation at 365 nm with methyl ketones to form (Cp*Ru) 2 (μ-H) 2 (μ–η 4 -CH 2 C­(O)­CHR) + 2H 2 where the bridging ligand is described as oxatrimethylenemethane . The authors propose that the reaction proceeds via an exciplex, although no further evidence is provided.…”
Section: Photochemical Processesmentioning
confidence: 99%
“…It also reacted photochemically with CpNi­(CO) 2 , CpCo­(CO) 2 , and [CpFe­(CO) 2 ] 2 to yield heterobimetallic clusters with different geometries. Although no mention was made of the primary photoprocess by the authors, elimination of H 2 from the tetrahydrido Ru-species is required for the observed product to be formed. ,, The only example of a polyhydride of osmium involved in a photochemical reaction is the photochemical reductive elimination of H 2 from Cp*Os­(H) 3 (CO) to form the dimer [Cp*Os­(CO)] 2 (μ-H) 2 …”
Section: Metal Hydride Photochemistry By Transition Metal Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we recently reported on the photoinduced bimetallic activation of 2-alkanones to afford dinuclear oxatrimethylenemethane complexes. 5 Our initial studies involved the synthesis of mixed-metal clusters with identical ligands on each metal atom to examine the effect of the metal atoms on the structure and reactivity of the cluster complexes. Thus far, we have synthesized a series of heterometallic polyhydrido clusters containing both the [Cp*Ru] moiety and Mo, W, 6 Re, 7 Os, 8 Co, 9 Rh, and Ir fragments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we reported photoinduced C–H bond cleavage of acetone, resulting in the formation of a dinuclear bridging oxatrimethylenemethane complex of ruthenium . This reaction is considered to be very typical of polyhydride-bridged cluster complexes, because the reaction mechanism does not involve either initial H 2 elimination or fragmentation of the cluster framework.…”
mentioning
confidence: 99%